Effects of different fertilization sources on Olea europaea (Oleraceae) - Mariano Andrés Busso; Liliana G. Suñer; Roberto A. Rodríguez (Lilloa, 2022)
This review highlights the importance of olive trees growing in the southwest of Buenos Aires, Argentina. It also discusses the importance (1) of the different fertilizations forms in the determination of the various soil physicochemical and leaf chemical properties, olives yield, oil yield and quality, and (2) oil quality parameters. Cover crops can be beneficial to soil properties. The incorporation of organic manures is also beneficial to improve plant and soil physical and biological properties, which allows a better root development and longevity, and nutrient absorption. Additionally, organic crops can increase the oil yield and quality in comparison to non-organic treatments. Foliar fertilization can be a very efficient system for supplying N, P and K to olive trees. However, several applications are required to meet the needs of the crop. Olive yield decreases significantly when soil fertilization with N is eliminated for several consecutive years in comparison to the fertilization that is carried out annually. Nutrient overfertilizationcan lead to several negative effects from the environmental point of view. Fertilization with P might be unnecessary due to the extensive root system of the olive trees. Olive have a high K requirement since large amounts of K are removed each year at harvest. However, fertilization with different levels of K had negligible effects on oil quality. Oil quality parameters were first associated with N concentrations in leaves and fruits. The phenolic content of the oil decreased linearly in relation to the increase of N in the leaves, which indicates a competition between the synthesis of proteins and the phenolic compounds.